1998
DOI: 10.1046/j.1472-765x.1998.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Light inactivation of food-related pathogenic bacteria using a pulsed power source

Abstract: The effects of high intensity light emissions, produced by a novel pulsed power energization technique (PPET), on the survival of bacterial populations of verocytotoxigenic Escherichia coli (serotype 0157:H7) and Listeria monocytogenes (serotype 4b) were investigated. Using this PPET approach, many megawatts (MW) of peak electrical power were dissipated in the light source in an extremely short energization time (about 1 ms). The light source was subjected to electric field levels greater than could be achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 3 publications
(3 reference statements)
3
62
0
1
Order By: Relevance
“…The efficiency of PL on inactivating bacteria, mold spores, and viruses is well documented (MacGregor et al 1997;Rowan et al 1999;Anderson et al 2000;Roberts and Hope 2003). The effects of PL on microorganisms in vitro are shown in Table 1.…”
Section: Microbial Inactivation By Plmentioning
confidence: 90%
See 1 more Smart Citation
“…The efficiency of PL on inactivating bacteria, mold spores, and viruses is well documented (MacGregor et al 1997;Rowan et al 1999;Anderson et al 2000;Roberts and Hope 2003). The effects of PL on microorganisms in vitro are shown in Table 1.…”
Section: Microbial Inactivation By Plmentioning
confidence: 90%
“…Photoreactivation in flashed cells was evident after PL treatment (Gómez-López et al 2005a), the rate of this photoreactivation after a PL treatment was slower than after a continuous UV treatment (Otaki et al 2003). In fact, some authors have taken the precaution of wrapping the Petri dishes in aluminum foil to avoid photoreactivation after PL treatments (MacGregor et al 1997;Rowan et al 1999;Anderson et al 2000).…”
Section: Microbial Inactivation By Plmentioning
confidence: 99%
“…Several studies have shown the ability of PL to inactivate Salmonella spp., Escherichia coli, E. coli O157:H7, Listeria monocytogenes and Listeria innocua in some products (Bialka & Demirci, 2008;Ozer & Demirci, 2006;Palgan et al, 2011;Sauer & Moraru, 2009;Uesugi & Moraru, 2009). The variability of results (2e8 log reductions) is most likely due to the different target microorganisms, the intensity of the treatment, and the properties of the substrates (MacGregor et al, 1998;Paskeviciute, Buchove, & Luksience, 2010;Sharma & Demirci, 2003;Woodling & Moraru, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the materials used and experimental conditions under which different studies were performed have given rise to variable results which render any comparison difficult. Data in the literature confirm the effects of light pulse treatment on agar surfaces (MACGREGOR et al, 1998;ROWAN et al, 1999;KRISHNAMURTHY et al, 2004). KRISHNAMURTHY and co-workers (2004) observed a 7.5 log reduction of Staphylococcus aureus in agar-seeded cells treated for 5 s or longer by pulsed UV light at an energy of 5.6 J cm -2 .…”
Section: Agar-seeded Cellsmentioning
confidence: 71%